Analysis of Marketing Strategies in Outpatient Services, Inpatient and Physiotherapy Services by Method Mix Marketing at Royal Prima Marelan Medan Hospital - Sri Lestari Ramadhani Nasution; Therry Prosperita Karnifani Wau; Chrismis Novalinda Ginting; Tan Suyono (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
The increasing number of hospitals every year causes competition between hospitals in providing health services to patients. Because that's the need to implement a marketing strategy. This study aims to analyze the marketing strategy of Royal Prima Marelan Hospital with the marketing mix strategy namely product, price, place/distribution, and promotion (4P). This study used a qualitative approach, this research was conducted at Royal Prima Marelan Hospital with time research was conducted from June 3 until completion. conducted by interviewing 14 informants, namely 1marketing and public relations management, 1 general practitioner, 1 head of administration, 1 head of inpatient room, 1 head of outpatient room, 1 physiotherapist, and 8 patients. Data collection techniques were carried out using interviews, data from hospitals and data from journals and books officially published in libraries. The data analysis that will be carried out is analyzing marketing strategies with marketing mix analysis. From the research results it is known that a specialist urologist and neurosurgeon are needed, and the number of nurses needs to be increased. The advantage of this hospital in the field of service products is that even though it is a type C hospital, it has quite a lot of specialist doctors. This hospital focuses on excellent trauma services, but still requires specialists in neurosurgery and urology. Royal Prima Marelan Hospital is also located on the side of the road which is very quickly accessible, but it needs to expand or expand the entrance and exit. In the field of promotion quite a lot and often done by the management and employees. However, more promotion is needed in the physiotherapy service product section. Keyword: Hospital manangement, Marketing mix